Management in teorija organizacij: Učbenik - Jagodič, Gregor; Gorenak, Mitja (University of Maribor Press, 2022)
The Management and Theory of Organizations: Textbook. The Management and Theory of Organizations textbook presents a collection of a total of ten chapters through which students will gain an overview of the basis of understanding management and the theory of organizations in tourism. The introductory three chapters are mainly focused on organization and concepts of organization in tourism. Thus, in the first chapter we focus on the evolutionary view of how we came to organizations in the first place, in the second we analyze how the tourism system is linked to organizational functioning and in the third chapter we very narrowly analyze the specifics of the tourism system itself and the coding used in the system. Further, the chapters focus more on managerial content, which, despite everything, is interwoven with cases directly related to tourism. Thus, in the chapters we find a basic presentation of what management is and who a manager is, what are the roles and tasks of a manager, and we conclude the whole with the complex relationship between management and ethics. The entire textbook is designed in such a way that the content is strongly interwoven with numerous exercises and examples that will enable students to gain an in-depth understanding of the selected content.